ENGLISH MEDIUM INSTRUCTION IN THE PRIVATE UNIVERSITIES IN BANGLADESH - Islam, Monjurul (Indonesian Journal of Applied Linguistics, 2013)
Abstract: As it is viewed English Medium Instruction (EMI) at tertiary level has emerged as a big educational issue in Bangladesh as well as many parts of the world. Hence, the present trend of Bangladeshi higher education has assessed some crucial reasons of the extended use of English as a medium of instruction. Although education researchers in other countries have worked in this area to understand this educational issue, there has been very little research on EMI at tertiary level in Bangladesh. That is why, this study reports a case study involving teachers and students in a private university in Bangladesh by critically examining the language practice and implementation of EMI policy within the context of Bangladeshi higher education. Based on the analysis of interview data, it is argued that through their language practices and beliefs students and teachers constructed their perception towards the accomplishment of EMI policy, educational choice and effectiveness of EMI policy. It is suggested that implications of MOI policies world-wide and the national level practices of students’ content knowledge and English proficiency development in a globalizing world where English is widely believed to hold mammoth prospective for individuals and societies because of its role in human capital development.